2021
DOI: 10.21203/rs.3.rs-910003/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Workplace Violence Against Healthcare Professionals in Thai Tertiary Hospitals

Abstract: Background: Thailand lacks evidence of the current prevalence of workplace violence (WPV) at tertiary hospitals. This study aimed to examine the prevalence of, perpetrators of, and factors associated with WPV against healthcare workers in excellent tertiary hospitals in Thailand.Methods: This was a mixed-methods study. A questionnaire was individually administered by an interviewer to 220 healthcare workers using a tablet with an online platforms, and the completion rate was 100%. The study was conducted from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…One common example is how healthcare practitioners may not be able to handle patients and their caregivers effectively in overcrowded situations, a common scenario in emergency departments. Similarly, Kueanongkhun et al ( 26 ) reported that workplace violence frequently occurred at the front desk of the emergency department because of the high number of patients and relatives there.…”
Section: Resultsmentioning
confidence: 99%
“…One common example is how healthcare practitioners may not be able to handle patients and their caregivers effectively in overcrowded situations, a common scenario in emergency departments. Similarly, Kueanongkhun et al ( 26 ) reported that workplace violence frequently occurred at the front desk of the emergency department because of the high number of patients and relatives there.…”
Section: Resultsmentioning
confidence: 99%